2013
DOI: 10.3174/ajnr.a3798
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Solitaire Stent-Assisted Coiling: A Technique for the Treatment of Acutely Ruptured Wide-Neck Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE:Wide-neck intracranial aneurysms in patients with acute SAH are often challenging lesions to treat by neurosurgical and endovascular approaches. The aim of this study was to investigate the feasibility, safety, and efficacy of the use of temporary Solitaire AB stent-assisted technique with coiling for the treatment of acutely ruptured wide-neck aneurysms without perioperative antiplatelet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Temporary stent placement with laser-cut intracranial stents has been described recently for ruptured aneurysms. 30 Our series demonstrated that this technique could be applied by using lowprofile braided stents. Furthermore, this technique can also be used in unruptured aneurysms when there is a high risk of rupture or catheter kickback during dual stent placement, as shown in our series.…”
Section: Discussionmentioning
confidence: 74%
“…Temporary stent placement with laser-cut intracranial stents has been described recently for ruptured aneurysms. 30 Our series demonstrated that this technique could be applied by using lowprofile braided stents. Furthermore, this technique can also be used in unruptured aneurysms when there is a high risk of rupture or catheter kickback during dual stent placement, as shown in our series.…”
Section: Discussionmentioning
confidence: 74%
“…These strategies have evolved from the early "microcatether transposition stent technique" and "stent stable microcatheter technique (Jailing)" to newly developed variable techniques, including semi-jailing, simple or multiple stenting for flow diversion, stent-jack, post-releasing, Y-stenting, waffle-cone stenting, and bailout or coil-jailing stenting techniques. 1) 2) 10) 12) 18) 19) 20) 24) 26) 34) 43) 44) 45) In our study, we mostly used the jailing technique, along with the stent-jack technique as a variation of the jailing technique. A major advantage of the jailing technique is an improvement in the stability against the kick-back and unstable movement of the microcatheter during coiling in intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described temporary stent-assisted coil embolization in patients with ruptured aneurysm using the Solitaire AB stent. Signorelli et al 43) and Almekhlafi et al 2) reported that retrieving the stent after coil embolization reduces the need for continued antiplatelet therapy and decreases the hemorrhagic risks associated with antiplatelet use. However, stent retrieval is not recommended in situations where a safety margin is not present or is hard to appreciate due to poor visualization of the stent.…”
Section: Discussionmentioning
confidence: 99%
“…Retrievability is a unique feature of the Solitaire AB stent that allows stent repositioning or removal if desired by the treating physician. 4 The goal of the study was to assess whether the characteristics of this device affected the benefits to the patient. Apart from retrievability, this set of characteristics cannot be individually evaluated, and their evaluation is reflected in the global results as safety and efficacy.…”
Section: Description Of Solitaire Ab Stent and Technical Aspectsmentioning
confidence: 99%